Multipotential hematopoietic blast colony-forming cells exhibit delays in self-generation and lineage commitment - Metcalf, Donald (National Academy of Sciences, 2010)
Murine hematopoietic blast colony-forming cells (BL-CFCs) are able to generate up to 30,000 progeny blast cells within 10 d in agar cultures. Contained in these populations are large numbers of lineage-committed progenitor cells in the granulocytic and macrophage lineages. Sequential analyses of blast colonies revealed that self-generation of BL-CFCs occurs but is surprisingly late in clonal expansion, as is the emergence of progenitor cells committed to megakaryocytic and eosinophil lineages. Self-generating BL-CFCs were highly enriched in lineage(−) Kit(+) Sca1(+) CD34(−) Flt3R(−) populations, and colonies generated by such cells contained colony-forming units–spleen and formed erythroid and lymphoid progeny in vivo. The data suggest the existence of a hierarchical structure in BL-CFC populations with at least a subset being cells assayable as colony-forming units–spleen. Because BL-CFCs can self-generate and are able to generate lymphoid and myeloid populations, BL-CFCs appear to be ideal cells in which to analyze the processes of self-generation and lineage commitment in clonal in vitro cultures.